A Parallel Programming and Emitting Scheme for High-Resolution Active-Matrix Micro-LED Displays - Zheng, Xin; Zeng, Haohang; Hu, Jiangbo; Han, Haotian; Liao, Congwei; Zhang, Shengdong (IEEE transactions on electron devices, 2025)
This article proposes a parallel programming and emitting (PPE) driving scheme for high-resolution active-matrix micro-LED (AM- μ LED) displays. The PPE scheme incorporates a 1 T-1 C frame buffer within each pixel, enabling grayscale data for the current frame to be programmed during the emission period of the preceding frame. Compared with the conventional sequential line-by-line programming and synchronous emission (SE), the proposed PPE scheme significantly increases the emission time per frame from less than 50% to over 90%, while also providing additional time for compensation to improve the accuracy of the driving current. To validate the feasibility of the PPE driving scheme, an analog pulsewidth modulation (A-PWM) pixel circuit was designed and fabricated using a-IGZO thin-film transistors (TFTs). The fabricated pixel circuit demonstrates a reliable PPE operation, and maintains a low driving current error rate below 2%, even under a TFT threshold voltage variation of ±3 V.